(untitled) (Journal of Health Sciences, 2018)
Background: Clinical mentors play an important role in the development of knowledge and the acquisition of competencies of different health professionals. The success of the entire mentoring process also depends on the professional and personal characteristics of the clinical mentor. The purpose of this study was to identify which professional and personal characteristics of clinical mentors are relevant to physiotherapy (PHT) and social gerontology (SG) students. Methods: The web survey was performed between January 20 and May 15, 2018, using the adapted version of the nursing clinical teacher effectiveness inventory. The final sample consisted of 100 PHT and SG students from one of the Slovenian Universities. Results: The competencies “explains clearly” (p ˂ 0.001) and “takes responsibility of own actions” (p = 0.023) were statistically significantly more relevant to PHT students than to the SG students. The competencies “explains clearly” (p ˂ 0.001), “demonstrates clinical skill and judgment” (p = 0.033), “takes responsibility of own actions” (p = 0.023), and “is self-critical” (p = 0.023), were statistically significantly more relevant to PHT than to the SG students, while the statements “discusses current development in his/her field” (p = 0.002), “communicates expectations of students” (p = 0.029), “demonstrates empathy” (p = 0.037), “demonstrates enthusiasm” (p = 0.005), and “has a good sense of humor” (p = 0.005) were statistically significantly more relevant to SG students. Conclusion: The contrast in responses reflects the differences in the nature of both professions: The predominantly instrumental nature of PHT and the predominantly expressive nature of SG.